Efficacy of an empowerment education intervention on substance use among adolesecents living in peri-urban communities in Abuja, Nigeria - Ojonuba, Shuaibu Hassana (2023)
Adolescence has been reported to be a critical risk period for initiating the use of substances which is the consumption of licit substances like alcohol and cigarette and illicit substances like marijuana and drugs. In Nigeria, research has shown a high prevalence of substance use among adolescents, however only a few intervention studies, mostly health education interventions, have been implemented in Nigeria to curb the issue. Empowerment education interventions have the potential to reduce adolescent substance use, but the few studies applying this have been in developed countries. This study was conducted to determine the effect of an empowerment education intervention on substance use and its risk and protective factors among adolescents living in peri-urban communities in Nigeria. An empowerment education intervention curriculum was developed based on Freire’s listen-dialogue-action framework, and then subjected to focus group discussions and expert reviews for review and validation. The final curriculum was tested using a quasi-experimental design conducted among 300 in-school adolescents from peri-urban communities in Abuja. Baseline, two weeks, and three months follow-up data on the effect of the intervention on substance use and its risk and protective factors (delinquency, self-esteem, self-efficacy, attitude to substance use, peer support, and depression), as identified by the problem behaviour theory, was collected. Chisquare test, independent t-test and ANOVA were conducted to determine the intervention’s effects on the study outcomes. Qualitative data was collected two weeks post-intervention to gain the participant’s perspectives. A 12-session intervention curriculum called “Teen Heroes Curriculum” was developed and tested. Quantitative data showed no effect of the intervention on substance use at two weeks follow up, however at three months follow up, the prevalence of substance use, and number of substances used among the intervention group was significantly lower than the control group. Among the intervention group, peer support at two-week follow up, delinquency and selfesteem at three months follow up were significantly different than the control group. Higher intervention attendance was associated with better attitude towards substance use and lower depression among the intervention group. Qualitative data showed that participants generally enjoyed the program, with many of them reporting gaining new knowledge, learning to work in teams, making new friends, and becoming more confident to share their views, and stopping substance use. Overall, the intervention showed potential to reduce substance use among adolescents, as well as influence its risk and protective factors, however it would probably have been more effective if it addressed familial factors. This study is the first to test the efficacy of an empowerment education intervention in Nigeria, therefore its findings provide valuable insight on its applicability among adolescents in low resource settings in Nigeria, and to practitioners on addressing substance use among adolescents in peri-urban communities.